General and precise carbon confinement of functional nanostructures derived from assembled metal–phenolic networks for enhanced lithium storage. Issue 38 (19th September 2018) - Xiao, Zhitong; Meng, Jiashen; Li, Qi; Zhang, Xiao; Liu, Ziang; Wen, Bo; Han, Chunhua; Mai, Liqiang
Abstract : A general and programmable strategy has been developed to precisely construct carbon-confined nanostructures via metal–phenolic network assembly, which then displayed excellent lithium storage. Abstract : Carbon coating strategies have been widely used to enhance the electrochemical performance of electrode materials. However, several issues, including substrate material selectivity, hard control on precise coatings and a limited enhancement of electronic conductivity, hinder the conventional strategies from further practical application. Here, we develop a general, facile and programmable strategy to precisely construct carbon-confined functional nanostructures with high conductivity via metal–phenolic network (MPN) assembly and subsequent controlled pyrolysis. The instantaneous MPN assembly is realized via the coordination reaction between metal ions and phenolic ligands, and the thickness of the MPN shell can be well controlled by simply repeating the rapid assembly procedure. This strategy is further successfully extended to versatile electrode materials with diverse nanostructures and rich compositions. As a proof of concept, the as-synthesized carbon-confined SnO2 hollow spheres with Fe2 O3 nanodots embedded in a carbon shell (SnO2 @C–Fe2 O3 ) exhibit a high reversible discharge capacity of 1203 mA h g −1 after 100 cycles at 0.2 A g −1, an excellent cycling stability with a capacity retention of 86% after 1000 cycles at 1 A g −1, and a high capacity of 830 mA h g −1 at a higher rate of 5 A g −1 . These remarkable performances are attributed to the unique carbon shell, which provides the robust structure to buffer the drastic volume variation and the enhanced electronic conductivity. This programmable and controllable carbon coating strategy opens a new avenue for the design of carbon-incorporated electrode materials for high-performance energy storage.